Quasiconformal mappings in octonionic algebra: A graphical and analytical comparison - Borges, M. F. [UNESP]; Benzatti, L. F L [UNESP] (My University, 2009)
In this article, we present quasiconformal mappings related to octonionic algebra. Based on the metric definition of quasiconformal mappings and using transformations of the type f(z)=zn, we compare the graphical and analytic results. © 2009 Pushpa Publishing House.
Keywords: Dilatation; Hypercomplex; Octonions; Quasiconformal